An overview of transport strategies in Malaysia - Wahab, Ibrahim; Yusoff, Mohd Nazaruddin; Talib, Azlizan (2016)
Many policies have been implemented on piecemeal approach over many years, further obscuring the cause effect relationship between policy and economic impact.As such it makes it extremely difficult to ascertain the extent of energy saving in implementing the formulated urban traffic plans.This paper examines ways and strategies to conserve energy with regard to transport planning